2022
DOI: 10.3748/wjg.v28.i22.2403
|View full text |Cite
|
Sign up to set email alerts
|

Prehabilitation prior to intestinal resection in Crohn’s disease patients: An opinion review

Abstract: Patients with Crohn’s disease (CD) are at a considerable risk for intestinal surgery. Approximately 25% of patients with CD will undergo an intestinal resection within 10 years of diagnosis. Postoperative complications after CD surgery have been reported in 20%-47% of the patients. Both general and CD-related risk factors are associated with postoperative complications, and comprise non-modifiable ( e.g., age) and potentially modifiable risk factors ( e.g., malnutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…Nutritional evaluations include muscle mass, assessment of dietary intake, gastrointestinal symptoms such as diarrhea, smoking cessation, weaning off steroids, and complete laboratory workup including C-reactive protein (CRP), complete blood count (CBC), micronutrient panel, and serum albumin. 13 Use of prehabilitation, including addressing pre-operative anemia, may have benefit in optimizing post-operative outcomes in elective surgery. The European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines suggest a minimum of 7-14 days of nutritional optimization and up to 6-8 weeks of nutritional support; the use of exclusive enteral nutrition (EEN) with a complete liquid diet of various compositions has been suggested as an effective pre-operative therapy with decreased inflammation and mucosal cytokines, reduction of post-operative complications, including abscesses and anastomotic leaks, and improvement of pre-operative albumin and nutrition levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional evaluations include muscle mass, assessment of dietary intake, gastrointestinal symptoms such as diarrhea, smoking cessation, weaning off steroids, and complete laboratory workup including C-reactive protein (CRP), complete blood count (CBC), micronutrient panel, and serum albumin. 13 Use of prehabilitation, including addressing pre-operative anemia, may have benefit in optimizing post-operative outcomes in elective surgery. The European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines suggest a minimum of 7-14 days of nutritional optimization and up to 6-8 weeks of nutritional support; the use of exclusive enteral nutrition (EEN) with a complete liquid diet of various compositions has been suggested as an effective pre-operative therapy with decreased inflammation and mucosal cytokines, reduction of post-operative complications, including abscesses and anastomotic leaks, and improvement of pre-operative albumin and nutrition levels.…”
Section: Discussionmentioning
confidence: 99%
“…The European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines suggest a minimum of 7-14 days of nutritional optimization and up to 6-8 weeks of nutritional support; the use of exclusive enteral nutrition (EEN) with a complete liquid diet of various compositions has been suggested as an effective pre-operative therapy with decreased inflammation and mucosal cytokines, reduction of post-operative complications, including abscesses and anastomotic leaks, and improvement of pre-operative albumin and nutrition levels. 13 Brennan and colleagues 14 in their meta-analysis note that CD patients with pre-operative enteral nutrition have significantly decreased post-operative complications with a number needed to treat of two. Grass et al note in their systematic-review enteral nutrition is again associated with decreased infectious complications and 30-day post-operative complications for Crohn’s patients.…”
Section: Discussionmentioning
confidence: 99%
“…Once the patient has been referred for surgery and surgery has been decided upon, it is the surgeons' role to directly optimize the patient the best they can, with nutritional supplementation, prehabilitation, and educating the patient on the operation and expected postoperative course as many anxieties of surgery are secondary to the unknowns surrounding the operation. 42 Once in the operating room, a minimally invasive approach should be attempted, if safe; however, the intra-abdominal pathology, such as fistulae, sepsis, or the thickness and friability of the mesentery will dictate if the operation can be completed minimally invasive, or if a hybrid or open approach will be needed for a safe operation. If the terminal ileum (TI) is grossly diseased, (i.e., adherent to the right lower quadrant retroperitoneum), it behooves the surgeon to start the dissection away from the involved tissue and "circle the pathology," typically by mobilizing the hepatic flexure and medializing the ascending colon and possibly the descending/sigmoid colon in the case of an ileosigmoid fistula.…”
Section: Patient-centric Approach and Intraoperative Decision-makingmentioning
confidence: 99%
“…33 Recently, the concept of formal prehabilitation programs to improve postoperative outcomes in frail patients has been highlighted, and the PREHAB randomized trial, and other studies, have shown promising results. 6,7,34 Anemia Anemia is another relatively common modifiable risk factor in patients with CD and may be related to nutritional deficiencies and blood loss from CD-related bleeding from ulcerations. A systematic review by Wilson et al showed the prevalence of anemia among patients with CD ranged from 10.2 to 72.7%.…”
Section: Sarcopenia and Frailtymentioning
confidence: 99%